PEMBARUAN KEBIJAKAN PUBLIK: MENUJU KEBIJAKAN BERBASIS PRAKARSA MASYARAKAT - Purwo Santoso (Populasi, 2004)
The backbone of the decentralization and democratization process in Indonesia is transforming to bring about participatory policy-making. In recognition of the degree of institutionalization left behind by the previous centralized authoritarian policy-making of the New Order Government, this article aims to identify the challenges that lie a head.